Tracheoesophageal Fistula Complicated by Iatrogenic Gastric Perforation in a Low Birth Weight Neonate - Gupta, Anju; Pande, Dimple; Kachru, Nishtha; Khan, Ahtesham (Journal of Nepal Health Research Council, 2020)
Type-III tracheoesophageal fistula is the commonest type of fistula where upper pouch is blind and distal oesophageal pouch communicates with trachea. In this condition, gastric distension is a common manifestation which can be worsened by positive pressure ventilation. Pulmonary pathology may necessitate ventilation with high peak airway pressures which may rarely lead to gastric perforation with serious consequences. We are reporting such a case of gastric perforation during ventilatory management for fistula repair which needed surgical repair. Keywords: Airway management; esophageal atresia; gastric perforation; tracheo-oesophageal fistula.